2018
DOI: 10.1021/acs.jpcc.8b07213
|View full text |Cite
|
Sign up to set email alerts
|

First-Principles Comparison of Proton and Divalent Copper Cation Exchange Energy Landscapes in SSZ-13 Zeolite

Abstract: The relative proximity of Al atoms substituted in zeolite lattices is an important parameter that influences both hydrothermal stability and catalytic function, but the underlying chemistry that governs Al site proximity is not well understood. Here, we examine relationships between exchanged countercations and different Al–Al arrangements in a chabazite (SSZ-13) zeolite lattice. We report periodic supercell density functional theory (DFT) calculations for structures and energies of SSZ-13 lattices with system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
62
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(67 citation statements)
references
References 60 publications
5
62
0
Order By: Relevance
“…Discrimination within these sets is more challenging. Samples prepared to contain only Z 2 Cu species potentially contain two geometrically distinct sites distinguished by the location of the charge-compensating Al, 80 and such sites are predicted here to have distinct UV-Vis spectra if computed at one minimum energy structure. Accounting for the nite temperature uctuations in Cu location between local minima and associated uctuations in Cu coordination environment, however, attenuates these differences, such that the two sites become spectroscopically indistinguishable.…”
Section: Discussionmentioning
confidence: 85%
“…Discrimination within these sets is more challenging. Samples prepared to contain only Z 2 Cu species potentially contain two geometrically distinct sites distinguished by the location of the charge-compensating Al, 80 and such sites are predicted here to have distinct UV-Vis spectra if computed at one minimum energy structure. Accounting for the nite temperature uctuations in Cu location between local minima and associated uctuations in Cu coordination environment, however, attenuates these differences, such that the two sites become spectroscopically indistinguishable.…”
Section: Discussionmentioning
confidence: 85%
“…here: as-made zeolites, containing OSDA, in equilibrium with their 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 synthesis liquor). 44,57 Zeotype materials kept within their synthesis liquor are known to be non-rigid: e.g. Si-islanding is a well-documented phenomenon in silicoaluminophoshates.…”
Section: Analysis Of Synthetic Factors Contributing To DCC Variationmentioning
confidence: 99%
“…43 Computational studies demonstrate the presence of 25 symmetrydistinct combinations within the CHA unit cell containing two Al atoms (Si/Al=17) and 210 possible combinations to counterbalance a divalent cation on these 25 configurations, due to the four possible acidic O F (framework oxygen) neighboring each Al. 44 The most stable combination, at least in certain conditions, is often found to be a divalent cation in square planar coordination on two opposite Al tetrahedra in a 6MR in SSZ-13 materials (Cu 2+ , 45 Co 2+ 43 and Fe 2+ 27-28 ). Di Iorio and Gounder pioneered synthetic control over the Aldistribution in SSZ-13 in the context of acid-catalyzed reactions (methanol to dimethylether).…”
Section: Introductionmentioning
confidence: 99%
“…Schneider and co-workers performed similar calculations and reported that, in general, the 4NN configuration is the least stable followed by 3NN and 2NN. 31 The geometries for 6MR-2NN and 6MR-3NN are shown in Figure 2. Since the energies of 8MR-2NN, 8MR-3NN, and 8MR-4NN are nearly the same, the structure of only one of them (8MR-4NN) is shown in Figure 2.…”
Section: Stability Of Various Al Configurations In the Chamentioning
confidence: 99%